2015
DOI: 10.1016/j.expneurol.2014.10.017
|View full text |Cite
|
Sign up to set email alerts
|

The role of the nitric oxide pathway in brain injury and its treatment — From bench to bedside

Abstract: Nitric oxide (NO) is a key signalling molecule in the regulation of cerebral blood flow. This review summarises current evidence regarding the role of NO in the regulation of cerebral blood flow at rest, under physiological conditions, and after brain injury, focusing on subarachnoid haemorrhage, traumatic brain injury, and ischaemic stroke and following cardiac arrest. We also review the role of NO in the response to hypoxic insult in the developing brain. NO depletion in ischaemic brain tissue plays a pivota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
221
1
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(267 citation statements)
references
References 108 publications
9
221
1
10
Order By: Relevance
“…[9][10][11] In preclinical studies, NO donors reduced lesion size and increased cerebral blood flow, but only if given early. 12 In multiple pilot randomized controlled trials, NO donors (specifically intravenous sodium nitroprusside and transdermal glyceryl trinitrate [GTN]) reduced BP, pulse pressure, variability, and peak systolic BP; maintained cerebral blood flow (in spite of BP reduction); and improved arterial compliance.…”
mentioning
confidence: 99%
“…[9][10][11] In preclinical studies, NO donors reduced lesion size and increased cerebral blood flow, but only if given early. 12 In multiple pilot randomized controlled trials, NO donors (specifically intravenous sodium nitroprusside and transdermal glyceryl trinitrate [GTN]) reduced BP, pulse pressure, variability, and peak systolic BP; maintained cerebral blood flow (in spite of BP reduction); and improved arterial compliance.…”
mentioning
confidence: 99%
“…It has been demonstrated that NO constitutes a potent endogenous vasodilator, which directly acts on vascular smooth cells, causing vascular relaxation [72]. In addition, NO also has neuroprotective function [73].…”
Section: Nitric Oxide (No)mentioning
confidence: 99%
“…In contrast, iNOS is mainly found in the microglia, astrocytes, macrophages and neutrofiles. It is not Ca 2+ -calmoduline -dependent, but its long activity defines the concentration of cytokines, as well as inflammatory and immunological stimulation [16,17]. [4] NO functions as a neurotransmitter in the peripheral and central nervous system (CNS), however, it is not like the typical neurotransmitter stored in the synaptic vesicles, but after its synthesis, it is quickly released to the synaptic cleft.…”
Section: Introductionmentioning
confidence: 99%